Oxidative stress and alteration of biochemical markers in liver and kidney by malathion in rat pups. (September 2015) - Selmi, Slimen; El-Fazaa, Saloua; Gharbi, Najoua
The present study was undertaken to determine the effects of malathion exposure through maternal milk on oxidative stress, functional an metabolic parameters in kidney and liver of rat pups. We found that lactational exposure to malation (200 mg/kg, body weight (bw)) induced an oxidative stress status assessed by an increase in malondialdhyde (MDA) content, reflecting lipoperoxidation, a decrease in thiol groups' content as well as depletion of enzyme activities as a superoxide dismutase (SOD) and catalase (CAT) on postnatal days (Pnds) 21 and 51. Moreover, the current study showed that malathion induced liver and kidney dysfunctions demonstrated by considerable increase in phosphatase alkaline (PAL), aspartate aminotransferase (AST) and alanine aminotransferase (ALT) activities as well as total and direct bilirubin, creatinine urea and acid uric contents. We also observed an increase in triglyceride (TG), total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and a decrease in high-density lipoprotein cholesterol (HDL-C) in the plasma of treated rat pups. These findings evidenced that malathion exposure during lactation through maternal milk of rats pups induced kidney and liver oxidative stress as well as functional and metabolic disorders that play a role in the development of others pathologies as cardiovascular diseases and cancers.